Mine filling material based on metallurgical solid waste and preparation method thereof
By preparing metallurgical solid waste filling materials with high compressive strength, the problems of solid waste accumulation and environmental pollution in the metallurgical process are solved, and the reuse of resources and sustainable environmental development are achieved.
Patent Information
- Application Number
- CN202411311352.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
AI Technical Summary
If large amounts of solid waste resources generated during the metallurgy process, such as steel tailings, blast furnace slag and tailings mud, are not properly disposed of, they will occupy land resources and pollute the environment. The traditional solidification method is costly and inefficient.
Using metallurgical solid waste-based mine filling materials, mixing gel materials with high compressive strength is prepared by preparing the mixing of gel materials and iron ore tailings mud for mine treatment and reducing solid waste accumulation and environmental pollution.
Effectively utilize metallurgical solid waste resources, reduce environmental pollution, reduce land occupation, improve the comprehensive utilization rate of solid waste, reduce production costs, and meet the use requirements of mine filling materials.
Smart Images

Figure CN119191798A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of mine management, and in particular to a mine filling material based on metallurgical solid waste and a preparation method thereof. Background Art
[0002] In today's society, the rapid development of industry has brought many challenges. Among them, the rapid development of the metallurgical industry has made great contributions to economic construction, but it has also generated a large amount of metallurgical solid waste resources. Steel tailings are one of the main wastes in the metallurgical process and have a huge output. These steel tailings usually contain a variety of metal oxides and other complex components. If not properly handled, they will not only occupy a large amount of land resources for stacking, but may also release harmful substances through wind erosion, water erosion and other processes under the influence of the long-term natural environment, causing pollution to the surrounding soil and water.
[0003] Blast furnace slag is also a solid waste product that cannot be ignored in the metallurgical process. The large amount of blast furnace slag accumulated, on the one hand, occupies precious arable land resources, reducing the land area that can be used for agricultural production and ecological construction; on the other hand, due to the complexity of its composition, it may undergo chemical reactions under certain conditions to produce harmful gases or leakages, posing a potential threat to the atmospheric environment and groundwater. At the same time, sulfur ash, as an environmental by-product of the metallurgical process, also faces treatment difficulties. If a large amount of desulfurization ash is simply piled up, it will not only waste space, but also may have adverse effects on the surrounding ecological environment due to the residual chemical components therein. At the same time, mining activities are continuing, and every year A huge amount of tailings slurry is generated every year. Due to its special physical properties and chemical composition, these tailings slurries cannot be directly backfilled. If the traditional solidification method is used to treat the tailings slurry, the cost is extremely high, which brings a heavy economic burden to mining companies. The large accumulation of tailings slurry not only occupies a large amount of land resources, but also may cause a series of environmental problems. For example, long-term accumulation of tailings slurry may leak into the ground, pollute groundwater sources, and affect the drinking water safety of surrounding residents. At the same time, under the influence of natural conditions such as rain erosion, harmful substances in the tailings slurry may enter the soil, causing soil pollution and affecting vegetation growth and ecological balance.
[0004] In order to solve the above problems, exploring the use of solid waste resources generated by metallurgy to prepare mine filling materials has become a very promising solution; this can not only effectively deal with the large amount of accumulated metallurgical solid waste, avoid its pollution to the environment and occupy precious space resources, but also enable the iron ore tailings slurry to be effectively filled and utilized, realize waste utilization, and promote resource recycling and sustainable development. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a mine filling material based on metallurgical solid waste and a preparation method thereof, which solves the problem that a large amount of metallurgical solid waste resources are generated in the metallurgical process and a large amount of tailings slurry is generated every year during the mining process, affecting land resources and the environment.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a mine filling material based on metallurgical solid waste, characterized in that it includes 5%-14% gel material and 86%-95% iron ore tailings mud; wherein the specific ratio of the gel material is 5%-10% activator, 5%-10% desulfurization ash, 10%-20% steel slag powder, and 60%-75% slag powder.
[0007] Preferably, the concentration of the iron ore tailings mud is 70%-75%.
[0008] A method for preparing a mine filling material based on metallurgical solid waste comprises the following steps:
[0009] S1. Prepare raw materials: prepare activator, desulfurization ash, steel slag powder, slag powder and iron ore tailings mud according to the proportion;
[0010] S2. Preparation of gel material: first pour the steel slag powder and slag powder into the mixing drum, and start the mixing drum to stir the steel slag powder and slag powder at a low speed, then slowly add the desulfurization ash after preliminary stirring, and continue stirring to make the desulfurization ash fully dispersed in the mixed powder, then sprinkle the activator evenly into the mixing equipment, increase the stirring speed to medium speed, and ensure that the activator can fully contact and react with other ingredients;
[0011] S3. Monitoring and adjustment: During the mixing process, take samples of the stirred samples at regular intervals for component testing to ensure that the proportions of the components meet the requirements. If a deviation in the proportion is found, add the missing materials in time to ensure the accuracy of the proportion;
[0012] S4. Mixing the gel material with the slurry: Adding the iron ore tailings mud to the stirred gel material in batches, and starting the mixer for 2-3 hours, wherein the ratio of the iron ore tailings mud to the gel material is 1:10;
[0013] S5. Molding and performance testing: Pour the mixed material into the mold and use a vibrator to vibrate it appropriately to expel the air in it and make the material more compact. Then, perform maintenance for a specified number of days. After the material is fully formed, take it out and perform a compressive strength test on it to ensure that its compressive strength reaches more than 2.5MPa and meets the user's requirements.
[0014] Preferably, the specific stirring speed in step S2 is: low-speed stirring is 30-50 revolutions per minute, and medium-speed stirring is 80-120 revolutions per minute.
[0015] Preferably, the specific stirring time in step S2 is: the steel slag powder and the slag powder are stirred at a low speed for about 5-10 minutes; the desulfurization ash is fully dispersed in the mixed powder for about 3-5 minutes; the activator is evenly sprinkled into the mixing equipment for about 8-10 minutes.
[0016] Preferably, the specific monitoring time in step S3 is every 5-6 minutes.
[0017] Preferably, the specific batching in step S4 is divided into 7-8 times, and the time interval between each addition of tailings mud is 15-20 minutes.
[0018] Preferably, the specific vibrator parameters in step S5 are: the vibrator use time is 3-8 minutes, and the vibrator frequency is 2000-5000 times / minute.
[0019] Preferably, the maintenance period specified in step S5 is 28-30 days.
[0020] An application of a mine filling material based on metallurgical solid waste, such as a mine filling material based on metallurgical solid waste as described in any one of claims 1-2, is applied in the field of mine management, especially in the field of metal mines and coal mines.
[0021] The present invention provides a mine filling material based on metallurgical solid waste and a preparation method thereof, which has the following beneficial effects:
[0022] 1. The present invention makes full use of metallurgical solid waste resources to prepare mine filling materials, effectively solving the problem of accumulation of solid wastes such as large amounts of steel tailings, blast furnace slag and desulfurization ash generated in the metallurgical process, reducing the occupation of precious arable land resources, reducing the degree of environmental pollution, and realizing the recycling of resources. It meets the requirements of sustainable development, can effectively improve the comprehensive utilization rate of steel tailings, digest desulfurization ash, and solve Anshan Iron and Steel's solid waste problem.
[0023] 2. The mine filling material of the present invention has a flexible formula. The proportions of the activator, desulfurization ash, steel slag powder and slag powder in the gel material, as well as the proportion of iron ore tailings mud can be adjusted according to different needs to adapt to different engineering scenarios and improve the applicability of the material.
[0024] 3. The present invention is provided with a monitoring and adjustment system, which can timely discover and adjust improper proportions through accurate sampling, analysis and calculation of material proportion deviations, thereby improving the quality of the finished product and ensuring that the quality of the products produced in the mixing equipment is more stable and meets the standards.
[0025] 4. The present invention is provided with a calculation module, which makes the detection and calculation of the missing materials in the sample more accurate, ensures the accuracy of the subsequent addition of materials, and prevents the occurrence of excessive addition of materials.
[0026] 5. The present invention further calculates the overall deviation by calculating the deviation of each component, so as to comprehensively and accurately grasp the overall situation of the material ratio, which helps to timely discover potential imbalance problems in the ratio. It can not only make rapid adjustments in the production process to avoid product quality degradation due to accumulated deviations, but also provide strong data support for optimizing production processes and formulas, thereby further improving the quality stability and reliability of mine filling materials, reducing production costs, and enhancing product competitiveness in the market. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a flow chart of the preparation method of the present invention;
[0028] Figure 2 It is a flow chart of the monitoring system of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Embodiment 1:
[0031] Please refer to the attached Figure 1 , an embodiment of the present invention provides a mine filling material based on metallurgical solid waste, including 9% gel material and 91% iron ore tailings mud;
[0032] The specific proportion of the gel material is 5% of activator, 5% of desulfurized ash, 20% of steel slag powder, 70% of slag powder, and the concentration of iron ore tailings mud is 70%.
[0033] A method for preparing a mine filling material based on metallurgical solid waste comprises the following steps:
[0034] S1. Prepare raw materials: prepare activator, desulfurization ash, steel slag powder, slag powder and iron ore tailings mud according to the proportion;
[0035] S2. Preparation of gel material: first pour the steel slag powder and slag powder into the mixing drum, and start the mixing drum to stir the steel slag powder and slag powder at a low speed for about 5-10 minutes. After preliminary stirring, slowly add desulfurization ash and continue stirring to fully disperse the desulfurization ash in the mixed powder for about 3-5 minutes. Then, sprinkle the activator evenly into the mixing equipment and increase the stirring speed to medium speed to ensure that the activator can fully contact and react with other ingredients. The stirring time is about 8-10 minutes, wherein the low-speed stirring is 30-50 revolutions per minute and the medium-speed stirring is 80-120 revolutions per minute.
[0036] S3. Monitoring and adjustment: During the mixing process, use the monitoring and adjustment system to take samples of the stirred samples every 5 minutes to test the composition to ensure that the proportion of each component meets the requirements. If a deviation in the proportion is found, add the missing materials in time to ensure the accuracy of the proportion;
[0037] The monitoring and regulating system comprises a sampling module, the sampling module samples the materials in the mixing device and transmits the extracted samples to the spectral analysis module, the sampling module is connected to a spectral analysis module, the spectral analysis module analyzes the proportion of the sample and compares the proportion of the sample with the specified proportion, the spectral analysis module is connected to a calculation module, the calculation module is responsible for accurately calculating the specific missing proportion quantity, and the calculation module is provided with a deviation formula for calculating each component and a formula for calculating the overall deviation, the calculation module is connected to a control feeding module, the control feeding module receives the conclusion from the calculation module, and opens the corresponding material discharge valve according to the conclusion to discharge and supplement the proportion;
[0038] The deviation formula for calculating each component is:
[0039] D i =C i -R i
[0040] Calculate the population deviation:
[0041]
[0042] in:
[0043] D i : represents a certain component deviation; C i : The actual mass fraction (percentage) of the i-th component in the sample; R i : The specified mass fraction (percentage) of the i-th component; n: represents the number of component types;
[0044] If you need to evaluate the degree of sample qualification, you can set a threshold. iWhen it is less than the threshold, the sample is qualified. i When it is greater than the threshold, the sample is unqualified and the composition needs to be adjusted;
[0045] S4. Mixing the gel material with the mud: Adding 70% iron ore tailings mud to the stirred gel material in batches, and starting the mixer for 2 hours, wherein the specific batches are divided into 7 times, and the time interval for adding tailings mud each time is 15-20 minutes, and the ratio of iron ore tailings mud to gel material is 1:10;
[0046] S5. Molding and performance testing: Pour the mixed material into the mold and use a vibrator to vibrate it appropriately to expel the air in it and make the material more compact. After 28 days of maintenance, the material is taken out after it is fully formed and the compressive strength test is performed on the material to ensure that its compressive strength reaches more than 2.5MPa and meets the user's requirements.
[0047] Beneficial effects of Example 1: Fully utilizes metallurgical solid waste resources, including steel slag powder, slag powder, desulfurization ash and activators, and recycles solid waste that may originally cause environmental pollution, reducing the occupation of arable land by solid waste stacking and the pollution to the environment. After a specific preparation method, the cementitious material and iron ore tailings mud are mixed in a ratio of 1:10. After 28 days of maintenance, the compressive strength can reach more than 2.5MPa, which meets the use requirements of mine filling and provides stable support for the mine.
[0048] Embodiment 2:
[0049] A mine filling material based on metallurgical solid waste, comprising 14% gel material and 86% iron ore tailings mud;
[0050] The specific proportion of the gel material is 10% of activator, 10% of desulfurized ash, 20% of steel slag powder, and 60% of slag powder.
[0051] On the basis of Example 1, steps S4 and S5 in a method for preparing a mine filling material based on metallurgical solid waste are changed:
[0052] S4. Mixing the gel material with the mud: Add 70% iron ore tailings mud to the stirred gel material in batches, start the mixer, and stir for 2 hours. The specific batches are divided into 7 times, and the time interval between adding tailings mud is 15-20 minutes each time. The ratio of iron ore tailings mud to gel material is 1:6.
[0053] S5. Molding and performance testing: Pour the mixed material into the mold and use a vibrator to vibrate it appropriately to expel the air and make the material more compact. The parameters of the vibrator are: the vibrator is used for 3-8 minutes, the frequency of the vibrator is 2000-5000 times / minute, and it is maintained for 28 days. After the material is fully formed, take it out and test its compressive strength to ensure that its compressive strength reaches 4.1MPa or more to meet the user's requirements.
[0054] Beneficial effect of Example 2: By adjusting the ratio of activator, desulfurization ash, steel slag powder and slag powder in the cementitious material, and changing the mixing ratio with iron ore tailings mud to 1:6, the compressive strength of the final product after 28 days of maintenance reaches more than 4.1 MPa, which is suitable for mine filling scenarios with higher strength requirements.
[0055] Embodiment three:
[0056] A mine filling material based on metallurgical solid waste, comprising 5% gel material and 95% iron ore tailings mud;
[0057] The specific proportion of the gel material is 10% of activator, 5% of desulfurized ash, 10% of steel slag powder, and 75% of slag powder.
[0058] On the basis of Example 1, steps S4 and S5 in a method for preparing a mine filling material based on metallurgical solid waste are changed:
[0059] S4. Mixing the gel material with the mud: Add 70% iron ore tailings mud to the stirred gel material in batches, start the mixer, and stir for 2 hours. The specific batches are divided into 7 times, and the time interval between adding tailings mud is 15-20 minutes each time. The ratio of iron ore tailings mud to gel material is 1:20.
[0060] S5. Molding and performance testing: Pour the mixed material into the mold and use a vibrator to vibrate it appropriately to expel the air in it and make the material more compact. After 28 days of maintenance, the material is taken out after it is fully formed and the compressive strength test is performed on the material to ensure that its compressive strength reaches more than 1.8MPa and meets the user's requirements.
[0061] Beneficial effects of Example 3: Efficient utilization of tailings mud, with cementitious materials accounting for only 5% and iron ore tailings mud accounting for as high as 95%, greatly improving the utilization rate of tailings mud, which is of great significance for the treatment of large amounts of tailings mud. At the same time, with a lower usage of cementitious materials, the product can still achieve a compressive strength of more than 1.8 MPa after 28 days of maintenance through reasonable proportioning and preparation methods, saving metallurgical solid waste resources.
[0062] Comparative experiment:
[0063] Experimental purpose: To compare the performance differences of mine filling materials based on metallurgical solid waste prepared in Example 1, Example 2 and Example 3
[0064] Experimental process:
[0065] Prepare the raw materials according to the material proportions of the three embodiments respectively: Embodiment 1: 9% gel material (5% activator, 5% desulfurization ash, 20% steel slag powder, 70% slag powder), 91% iron ore tailings mud, and the concentration of tailings mud is 70%. Embodiment 2: 14% gel material (10% activator, 10% desulfurization ash, 20% steel slag powder, 60% slag powder), 86% iron ore tailings mud, and the concentration of tailings mud is 70%. Embodiment 3: 5% gel material (10% activator, 5% desulfurization ash, 10% steel slag powder, 75% slag powder), 95% iron ore tailings mud, and the concentration of tailings mud is 70%.
[0066] 1. Compressive strength test:
[0067] A plurality of test pieces are randomly selected from the cured materials of Example 1, Example 2 and Example 3, respectively, to ensure that the number of test pieces of each example is not less than 5, so as to improve the accuracy of the test results.
[0068] Place the specimen steadily on the workbench of the pressure testing machine, ensuring that the center of the specimen is aligned with the loading center of the pressure testing machine.
[0069] Start the pressure testing machine, apply pressure to the specimen at a constant loading rate (0.5 MPa per minute) until the specimen fails, and record the pressure value at the time of failure.
[0070] The pressure values of the five specimens of Example 1 at the time of failure were 2.6 MPa, 2.7 MPa, 2.5 MPa, 2.8 MPa, and 2.9 MPa, respectively, and the calculated average value was 2.7 MPa;
[0071] The pressure values of the five specimens of Example 2 at the time of failure were 4.2 MPa, 4.3 MPa, 4.1 MPa, 4.4 MPa, and 4.5 MPa, respectively, and the calculated average value was 4.3 MPa;
[0072] The pressure values of the five specimens of Example 3 at the time of failure were 1.9 MPa, 1.8 MPa, 2.0 MPa, 1.85 MPa, and 1.75 MPa, respectively, and the calculated average value was 1.86 MPa.
[0073] in conclusion:
[0074] The results show that the compressive strength of Example 2 is the highest, followed by Example 1, and Example 3 is the lowest.
[0075] This indicates that the higher content of gel material in Example 2 is helpful to improve the compressive strength of the material.
[0076]
[0077]
[0078] 2. Liquidity test:
[0079] A plurality of test pieces are randomly selected from the cured materials of Example 1, Example 2 and Example 3, respectively, to ensure that the number of test pieces of each example is not less than 5, so as to improve the accuracy of the test results.
[0080] Wet the inner wall of the slump cone and place it on a flat surface, making sure it is firmly in place.
[0081] The mixed materials of Example 1, Example 2 and Example 3 were respectively placed into the slump cone in three layers, and each layer was tamped 25 times with a tamping rod, and the tamping should be carried out from the outside to the center along the spiral direction.
[0082] After filling, use a spatula to scrape off excess material so that the top of the slump cone is flush with the surface of the material.
[0083] Lift the slump cone vertically and slowly to allow the material to collapse naturally under the action of gravity.
[0084] The height of the material collapse was measured with a ruler, which was the slump value. Each example was measured 5 times, and the average value was taken as the fluidity index of the example.
[0085] After measurement, the average slump value of Example 1 is 200 mm, the average slump value of Example 2 is 180 mm, and the average slump value of Example 3 is 160 mm.
[0086] in conclusion:
[0087] The fluidity of Example 2 is the best, probably because its higher content of gel material makes the material more uniform and easy to flow. The fluidity of Example 3 is relatively poor.
[0088] Example Fluidity (slump value, mm) Embodiment 1 200 Embodiment 2 180 Embodiment 3 160
[0089] 3. Setting time test:
[0090] The materials of Example 1, Example 2 and Example 3 were respectively loaded into standard test molds according to standard methods.
[0091] Place the test mold containing the material on the base of the Vicat instrument and adjust the pointer of the Vicat instrument.
[0092] Start timing from the time water is added and observe the changes in the state of the material.
[0093] When the material begins to lose its plasticity, the time recorded at this time is the initial setting time.
[0094] Continue to observe, when the material completely loses plasticity, record the time at this time as the final setting time. Each example is tested 3 times, and the average value is taken as the setting time of this example.
[0095] Assume that after testing, the initial setting time of Example 1 is 3 hours, and the final setting time is 5 hours; the initial setting time of Example 2 is 3.5 hours, and the final setting time is 6 hours; the initial setting time of Example 3 is 2.5 hours, and the final setting time is 4.5 hours.
[0096] Conclusion: Example 3 has the shortest setting time, which may be due to the fact that its higher content of activator accelerates the hydration reaction of the material. Compared with Example 1, Example 2 has the longest setting time.
[0097] Example Initial setting time (hours) Final setting time (hours) Embodiment 1 3 5 Embodiment 2 2.5 4.5 Embodiment 3 3.5 6
[0098] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A mine filling material based on metallurgical solid waste, characterized in that: It includes 5%-14% gel material and 86%-95% iron ore tailings mud; the specific proportion of the gel material is 5%-10% activator, 5%-10% desulfurization ash, 10%-20% steel slag powder, and 60%-75% slag powder.
2. A mine filling material based on metallurgical solid waste according to claim 1, characterized in that: The concentration of iron ore tailings mud is 70%-75%.
3. A method for preparing a mine filling material based on metallurgical solid waste according to any one of claims 1 to 2, comprising the following steps: S1. Prepare raw materials: prepare activator, desulfurization ash, steel slag powder, slag powder and iron ore tailings mud according to the proportion; S2. Preparation of gel material: first pour the steel slag powder and slag powder into the mixing drum, and start the mixing drum to stir the steel slag powder and slag powder at a low speed, then slowly add the desulfurization ash after preliminary stirring, and continue stirring to make the desulfurization ash fully dispersed in the mixed powder, then sprinkle the activator evenly into the mixing equipment, increase the stirring speed to medium speed, and ensure that the activator can fully contact and react with other ingredients; S3. Monitoring and adjustment: During the mixing process, take samples of the stirred samples at regular intervals for component testing to ensure that the proportions of the components meet the requirements. If a deviation in the proportion is found, add the missing materials in time to ensure the accuracy of the proportion; S4. Mixing the gel material with the slurry: Adding the iron ore tailings mud to the stirred gel material in batches, and starting the mixer for 2-3 hours, wherein the ratio of the iron ore tailings mud to the gel material is 1:10; S5. Molding and performance testing: Pour the mixed material into the mold and use a vibrator to vibrate it appropriately to expel the air in it and make the material more compact. Then, perform maintenance for a specified number of days. After the material is fully formed, take it out and perform a compressive strength test on it to ensure that its compressive strength reaches more than 2.5MPa and meets the user's requirements.
4. The method for preparing a mine filling material based on metallurgical solid waste according to claim 1, characterized in that: The specific stirring speed in step S2 is: low-speed stirring is 30-50 revolutions per minute, and medium-speed stirring is 80-120 revolutions per minute.
5. The method for preparing a mine filling material based on metallurgical solid waste according to claim 1, characterized in that: The specific stirring time in step S2 is: the steel slag powder and the slag powder are stirred at a low speed for about 5-10 minutes; the desulfurization ash is fully dispersed in the mixed powder for about 3-5 minutes; the activator is evenly sprinkled into the mixing equipment for about 8-10 minutes.
6. The method for preparing a mine filling material based on metallurgical solid waste according to claim 1, characterized in that: The specific monitoring time in step S3 is every 5-6 minutes.
7. The method for preparing a mine filling material based on metallurgical solid waste according to claim 1, characterized in that: The specific batching in step S4 is divided into 7-8 times, and the time interval between adding tailings mud each time is 15-20 minutes.
8. The method for preparing a mine filling material based on metallurgical solid waste according to claim 1, characterized in that: The specific parameters of the vibrator in step S5 are: the use time of the vibrator is 3-8 minutes, and the frequency of the vibrator is 2000-5000 times / minute.
9. The method for preparing a mine filling material based on metallurgical solid waste according to claim 1, characterized in that: The maintenance period specified in step S5 is 28-30 days.
10. An application of mine filling materials based on metallurgical solid waste, characterized in that: The mine filling material based on metallurgical solid waste as described in any one of claims 1-2 is used in the field of mine management, especially in the field of metal mines and coal mines.
Citation Information
Patent Citations
High strength silica powder concrete and construction technology
CN101538137A
Alkali-activated fly-ash filling material and preparation method thereof
CN104829200A
Method for preparing mine filler by cementing solid wastes in iron and steel industry with heavy metal tailings
CN112279565A
Self-flow type cemented filling material containing superfine tail mud, preparation method and application thereof
CN112897971A
Application type cemented filling material containing superfine tail mud as well as preparation method and application thereof
CN113087480A
Cited By
Mine backfill material based on metallurgical solid wastes and preparation method therefor
WO2026060880A1
